Get In The Ring: Professional Wrestling and Heavy Metal Music in Parallel - Cenate Pruitt (Journal of Public and Professional Sociology)
The sociological study of commonalities between professional wrestling and heavy metal music seems intuitive. Both are considered loud, flashy, and aggressively macho. Both have seen an explosion of critical academic analysis in the last decade. Both are perfect embodiments of what Barthes (1956) called “the spectacle of excess”. And yet, no academic research has explicitly brought the two together until now. This article serves as a beachhead, to first establish commonalities between the two forms, and then to explore the specific ways in which heavy metal culture has both infiltrated and been co-opted by mainstream American professional wrestling in the modern era (1985-present). By exploring successful and failed attempts to marry metal and wrestling, I argue that the heightened sense of authenticity central to both heavy metal and professional wrestling makes seemingly obvious cross-promotions difficult to achieve.